The Nandi is never far from Shiva - Brig. Ajai Singh (Jio Institute, 2021)
Nandi (bull) is Lord Shiva's vahana (mount) and companion. In Hindu scriptures, Nandi is the bearer of truth and righteousness. Each Hindu god has their own vahana (the Sanskrit root word for the English term of Wagon) that they use in war or in peacetime. Each of these vehicles stand for specific qualities that are consistent with the deity’s image and functions. Nandi signifies strength, load bearing capacity and virility.